Indonesian Gen Z's English slang: The use and effects on digital communication - Elly Nurhaliza Putri; Nanang Zubaidi; Yusnita Febrianti; Alma Huwaida Ramadhani; Sibakhul Milad Malik Hidayatulloh (Universitas Islam Malang, 2026)
The rapid expansion of social media transformed communication, encouraging the emergence of slang as a creative, identity-driven linguistic practice among Generation Z (Gen Z). Previous studies extensively examined types, functions, and general impacts of slang, presenting contradictory conclusions, either its positive role or negative implications. These inconsistent findings make it difficult to understand the actual role of English slang in communication effectiveness. However, limited research examined how Indonesian Gen Z use English slang and how it affects communication effectiveness among Gen Z users with similar linguistic backgrounds and comparable English proficiency. Addressing this gap, the present study investigates the types of English slang used by Indonesian Gen Z majoring in English studies in communication and analyzes its effects on clarity and effectiveness. With a qualitative-descriptive approach, data were collected through questionnaires (N=65) and semi-structured interviews with selected participants (n=6). The collected slang was categorized using a slang taxonomy and analyzed in relation to perceived message clarity and effectiveness. The findings reveal four types of slang: fresh and creative, flippant, acronym, and clipping. Acronyms were reported as the most frequently used slang in communication. The interviews indicate participants perceive slang as having positive impacts on communication effectiveness, self-expression, vocabulary development, and strengthening solidarity. However, the use of slang causes misunderstandings for those unfamiliar with slang and may encourage its inappropriate use in formal contexts. Future research should involve more diverse participant groups and examine the long-term effects of English slang on language use and communication.